Repurposing of auranofin and honokiol as antifungals against Scedosporium species and the related fungus Lomentospora prolificans. Issue 1 (1st January 2021) - Yaakoub, Hajar; Staerck, Cindy; Mina, Sara; Godon, Charlotte; Fleury, Maxime; Bouchara, Jean-Philippe; Calenda, Alphonse
ABSTRACT: The slowing-down de novo drug-discovery emphasized the importance of repurposing old drugs. This is particularly true when combating infections caused by therapy-refractory microorganisms, such as Scedosporium species and Lomentospora prolificans . Recent studies on Scedosporium responses to oxidative stress underscored the importance of targeting the underlying mechanisms. Auranofin, ebselen, PX-12, honokiol, and to a lesser extent, conoidin A are known to disturb redox-homeostasis systems in many organisms. Their antifungal activity was assessed against 27 isolates belonging to the major Scedosporium species: S. apiospermum, S. aurantiacum, S. boydii, S. dehoogii, S. minutisporum, and Lomentospora prolificans . Auranofin and honokiol were the most active against all Scedosporium species (mean MIC50 values of 2.875 and 6.143 μg/ml, respectively) and against L. prolificans isolates (mean MIC50 values of 4.0 and 3.563 μg/ml respectively). Combinations of auranofin with voriconazole or honokiol revealed additive effects against 9/27 and 18/27 isolates, respectively. Synergistic interaction between auranofin and honokiol was only found against one isolate of L. prolificans . The effects of auranofin upon exposure to oxidative stress were also investigated. For all species except S. dehoogii, the maximal growth in the presence of auranofin significantly decreased when adding a sublethal dose of menadione. The analysis of the expression of genes encoding oxidoreductase enzymes upon exposure of S. apiospermum to honokiol unveiled the upregulation of many genes, especially those coding peroxiredoxins, thioredoxin reductases, and glutaredoxins. Altogether, these data suggest that auranofin and honokiol act via dampening the redox balance and support their repurposing as antifungals against Scedosporium species and L. prolificans .